Analisis Penggunaan Aplikasi Pembelajaran Interaktif di SMP Swasta Idanoi - Nurman Samehuni Gea; Edwin Budianto Gulo; Seppy Putra Kasih Lase; Noveri Amal Jaya Harefa (Departement of Mathematics Education, 2024)
This research aims to analyze the use of interactive learning applications at Idanoi Private Middle School. This research uses a quantitative descriptive method with data collection techniques through questionnaires distributed to 100 students in grades VII and VIII. The research results show that the majority of students (80%) have used interactive learning applications, with the most frequently used applications being Google Classroom (50%), YouTube (40%), and Khan Academy (10%). The main motivation for students to use interactive learning applications is to help them understand lesson material (70%), increase interest in learning (20%), and complete assignments (10%). The main obstacles to using interactive learning applications are limited internet access (40%), lack of knowledge about interactive learning applications (30%), and expensive costs (20%). Based on the research results, it was concluded that interactive learning applications have the potential to improve the quality of learning at Idanoi Private Middle School.